Immune system participates in brain regeneration and restoration of reproduction in the earthworm Dendrobaena veneta. Issue 2 (October 2015) - Molnar, Laszlo; Pollak, Edit; Skopek, Zuzanna; Gutt, Ewa; Kruk, Jerzy; Morgan, A. John; Plytycz, Barbara
Highlights Restoration of cocoon production is a biomarker of brain regeneration in earthworms. Brains extirpated in Prilocaine anesthetized (PE) or electrostimulated (VE) worms. Coelomocytes were depleted in VE but not PE worms. Brains and reproduction were restored faster in PE than in VE worms. Coleomocytes participate in brain regeneration.